Colistin Utilization Evaluation in a Major Teaching Hospital in Iran - Nader Rezaie; Maryam Farasatinasab; Nasim Vaiszadeh; Mahin Jamshidi; Mitra Ranjbar; Zeynab Yasin; Behrooz Ghanbari; Nashmin Pakdaman (Research Center for Rational Use of Drugs (RCRUD), 2018)
Objectives: Colistin is an old antibacterial agent which is used in multiple drug resistant (MDR) infections. Due to increased rate of MDR infections, the use of this agent is raised in worldwide. The aim of this study was to identify colistin utilization patterns in a teaching hospital and to demonstrate the importance of the need to reconsider prescribing strategies for colistin administration. Methods: This retrospective cross-sectional study was performed between Augusts 2017and December 2017 at Firoozgar hospital affiliated to Iran University of Medical Sciences, Tehran, Iran. All colistin prescriptions for adult patients during the study period were enrolled for appropriateness evaluation according to the Lexi comp acquired by Wolters Kluwer and NHS guideline. Results: Among 70 patients who received colistin, pneumonia (70%) was the chief indication of colistin prescription. In 93% of cases, colistin was prescribed according to microbiological laboratory results. In 14% of patients, colistin administration was before providing microbiological laboratory evidence. Seventeen percent of the patients received loading dose of colistin. The indication of colistin therapy was inappropriate in 16% of patients.  The initial and end dose, and duration of treatment of colistin were appropriate in 20%, 40%, and 52% of patients, respectively. Among 70 cases, 24 (34%) and 36 (51%) patients required dose adjustment in first and end dose of colistin therapy which only dose correction was performed in 13 (18%) and 15 (21%) cases, respectively.    Conclusions: These findings, along with aforementioned guidelines supports the requirement for physicians' educational programs, proper strategies for appropriate prescriptions.